Postoperative immune response and surgical stress in selective neck dissection: Comparison between endoscopically assisted dissection and open techniques in cT1-2N0 oral squamous cell carcinoma - Fan, Song; Zhong, Jiang-long; Chen, Wei-xiong; Chen, Wei-liang; Li, Qun-xing; Wang, You-yuan; Lin, Zhao-yu; Zhang, Han-qing; Zhang, Da-ming; Yu, Xin; Liang, Fa-ya; Huang, Xiao-ming; et al. (Elsevier, 2017)
Background Endoscopically assisted selective neck dissection (SND) has recently been applied in clinical N0 cases of oral squamous cell carcinoma (OSCC). However, nothing is known of the immune response after surgery. Methods A total of 60 patients with cT1-2N0 OSCC randomly underwent endoscopically assisted SND and open operations. The serum levels of IL-6, IL-8, IL-10, IL-1b, TNF-a, CRP, cortisol, ACTH, and growth hormone were analyzed before the start of the surgery (T0) and at 2 (T1), 6 (T2), 24 (T3), and 72 h (T4) after surgery. Results A total of 31 patients were randomized for endoscopic SND, whereas 29 underwent open procedures. The release of IL-6, IL-10 and CRP was significantly lower in the endoscopic group than in the open surgery group (p < 0.05), and cortisol levels were also lower in the endoscopic group (p < 0.05). Conclusions Endoscopic SND could effectively provide lower inflammatory responses and surgical stress, reducing peri-operative trauma and accelerating recovery.
Keywords: Endoscopically assisted selective neck dissection; Immune response; Oral squamous cell carcinoma; Surgical stress